Influence of Mass Asymmetry on Nuclear Reaction Dynamics - Kaur, Deepinder (My University, 2011)
The present work deals with the theoretical study of multifragmentation and its associated phenomena in heavy –ion collision at intermediate energies. We present a complete systematic theoretical study of multifragmentation for asymmetric colliding nuclei for heavy-ion reactions in the energy range between 50 MeV/nucleon and 1000 MeV/nucleon by using soft equations of state. This study is performed within an isospin dependent quantum molecular dynamics (IQMD) model. We envision an interesting outcome for asymmetric colliding nuclei. Although nearly symmetric nuclei depict a well-known trend for rising and falling for the production of intermediate mass products, this trend, however, is completely missing for large asymmetric nuclei. Also the effect of isospin independent cross section has been studied. We have found the pronounced effect different cross section and mass asymmetry on the nuclear reaction dynamics.
M.Sc. (SPMS)
Keywords: Multifragmentation; Mass Asymmetry